ANALISIS PENGARUH KELENGKAPAN PENGISIAN FORMULIR CATATAN PERKEMBANGAN PASIEN TERINTEGRASI PASIEN CHEMOTERAPHY RAWAT INAP TERHADAP INSIDEN KESELAMATAN PASIEN DI RUMAH SAKIT UMUM PUSAT (RSUP) SANGLAH DENPASAR - Ni Yunita Nara Putri; Bambang Hadi Kartiko; Agus Donny Susanto (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTChemotheraphy action is one of the drugs that need to be watched for because it is classified as a high risk drug so that the CPPT chemotheraphy patient must be completely fulfilled. Based on observations, it was found incomplete CPPT of 504 records. This study aims to determine the effect of completeness of the CPPT form filling of hospitalized chemotheraphy patients towards patient safety incidents in Sanglah Hospital Denpasar. The research design used was descriptive qualitative analytic with cross sectional type of research. The sample in this study amounted to 274 medical records of inpatient chemotheraphy patients with 1370 records at Sanglah Hospital Denpasar. This research was conducted using a checklist and an interview. Research conducted from January 1 to December 31, 2018 produced data on the highest CPPT incompleteness rate of 63.13% in the documentary review, second place of 30.65% was found in the review of an important report, third place was 21.16% in the review authentication, and fourth place 4.37% at the identification review. This shows that completeness of filling in CPPT forms for inpatient chemotheraphy patients can affect the risk of patient safety incidents. The conclusion of this study is that there is an influence between patient safety incidents with identification review of 4.37%, important reports review of 30.65%, authentication review of 21.16% and documentation review of 63.13%.Keywords: chemotheraphy, integrated patient development notes, patient safety incidentsABSTRAKTindakan chemotheraphy merupakan salah satu obat yang perlu diwaspadai karena tergolong obat risiko tinggi sehingga CPPT pasien chemotheraphy harus diisi dengan lengkap. Berdasarkan hasil observasi ditemukan CPPT yang tidak lengkap sebesar 504 pencatatan. Penelitian ini bertujuan untuk mengetahui pengaruh kelengkapan pengisian formulir CPPT pasien chemotheraphy rawat inap terhadap insiden keselamatan pasien di RSUP Sanglah Denpasar. Rancangan penelitian yang digunakan adalah deskriptif analitik kualitatif dengan jenis penelitian cross sectional. Sampel dalam penelitian ini berjumlah 274 rekam medis pasien chemotheraphy rawat inap dengan 1370 pencatatan di RSUP Sanglah Denpasar. Penelitian ini dilakukan dengan menggunakan checklist dan wawancara. Hasil penelitian pada 1 Januari – 31 Desember 2018 didapatkan angka ketidaklengkapan CPPT tertinggi sebesar 63,13% pada review pendokumentasian, urutan kedua sebesar 30,65% pada review laporan yang penting, urutan ketiga sebesar 21,16% pada review autentifikasi, dan urutan keempat sebesar 4,37% pada review identifikasi hal ini menunjukan bahwa kelengkapan pengisian formulir CPPT pasien chemotheraphy rawat inap dapat mempengaruhi risiko terjadinya insiden keselamatan pasien. Kesimpulan dalam penelitian ini adalah adanya pengaruh antara insiden keselamatan pasien dengan review identifikasi sebesar 4,37%, review laporan yang penting sebesar 30,65%, review autentifikasi sebesar 21,16% dan review pendokumentasian sebesar 63,13%.Kata kunci: chemotheraphy, catatan perkembangan pasien terintegrasi, insiden keselamatan pasien.